A survey of in-service training needs of secondary school administrators Region IV [i.e. Region VI] - Western Visayas - Cuesta, Lilia R.
Data from 96 principals/assistant principals from 97 public high schools and 71 principals/assistant principals from 80 private schools were analyzed using percentages, means, ranking, Pearson's r, chi-square, t-test and F-test. Majority of the respondents want to undergo training for a degree at the University of the Philippines. Of the top ten skills perceived as most needed by the respondents, 50 are technical, 30 are conceptual, and 20 are human relations skills. Significant relationships were found among training needs and perceived tasks.